Diversity of Roman Catholics in Poland and their socio-institutional preferences - Turska-Kawa, Agnieszka (Religio, 2017)
The specific role of Roman Catholicism in Poland is associated both with over a thousand year's history of communion between religion and the state and with contemporary events, including, e.g., the collapse of communism, systemic transformation, and the selection of Karol Wojtyła as the pope. Because of these events, the sacred and secular spheres in Poland are not autonomous and often overlap. What is interesting, despite the commonly stressed religious homogeneity of Polish society, our research shows various internal paradoxes within that segment. This fact inspired us to carry out the presented research, aimed at verifying the internal coherence of the segment of people identifying as Roman Catholics, and at determining - on the basis of potential differences between them - the models of religious functioning in Poland. Due to the overlapping of the spheres of religion and politics in Polish history, we analysed the relations between the identified models and the desired types of socio-political order in the country. The analysis was influenced by anticipations concerning the impact of the model of religious functioning on the desired socio-political order in Poland, which may refer to the needs and values generated by the sphere of the sacred in different ways. Empirical findings show that generally in Poland there are three models of coexistence of the religious and secular orders: protesters, inclusionists, and fundamentalists. The outcome clearly proves the existence of strong relations between the models of religious functioning and the socio-political orders.